Anti-Bullying Values ​​in the Qur'an: A Thematic Interpretation Analysis and Their Implementation in the School Environment - Alaika Abdi Muhammad; Ahmad Rifqi Azmi (Interpersonal: Jurnal Bimbingan Konseling Islam, 2026)
This study aims to examine anti-bullying values in the Qur’an through a thematic interpretation (maudhu‘i) approach and analyze their implications for educational practices in school environments. Bullying has become a serious issue in Indonesian education due to its negative impact on students’ psychological, social, and academic development. Therefore, a strong value-based foundation is necessary to foster a safe and character-oriented school culture. This research employs a qualitative method with a library research design. The primary data consist of Qur’anic verses related to prohibitions against mocking, degrading others, calling people by offensive nicknames, and engaging in aggressive behavior. These verses are analyzed using thematic interpretation by referring to classical and contemporary exegeses. Furthermore, the identified values are integrated with character education theory to assess their relevance in bullying prevention efforts within schools. The findings reveal that the Qur’an explicitly prohibits all forms of behavior that lead to bullying—whether verbal, social, or psychological—and emphasizes respect for human dignity, empathy, brotherhood, and justice. These values are highly relevant for implementation in education through strengthening character education, promoting teacher role models, and cultivating an inclusive school culture. This study is expected to contribute conceptually to the development of education grounded in Qur’anic values in order to minimize bullying practices within educational settings.